Evaluation of the integration of AGoRA exoskeleton and T.FLEX orthosis (2021)
People who suffer from stroke have a higher difficulty performing basic activities of daily living (ADLs). This could affect a person’s quality of life. New technologies have been developed in rehabilitation to meet the needs of people and assist or rehabilitate the limb affected by hemiplegia. Exoskeletons in rehabilitation are designed to allow patients to walk naturally again. This is achieved by re-teaching the brain and muscles the different movements on the gait phases. Lower-limb exoskeletons are essential as they can lead to improve a person’s ability to walk, applying different assistive joint torques. This study evaluates the integration of a unilateral hip and knee exoskeleton and a T-FLEX robotic orthosis qualitatively and quantitatively in non-pathological users. Four subjects presented 6 different tests on a treadmill for 6 minutes: without the devices, with the AGoRA exoskeleton, with the integration of the AGoRA exoskeleton and the T-FLEX orthosis and hip stiffness variability tests consisting of: no stiffness, 10N preload and 15N preload. This population performed the tests 2 times where 2 different interfaces of the exoskeleton were tested. This is done in order to compare the performance of the devices with the same subjects under the two proposed interfaces which are mainly differentiated by the distribution of the weight of the exoskeleton and the grip it exerts on the body. It can be observed that there is a significant muscle activity reduction of 22% when integrating the T-FLEX orthosis to the AGoRA exoskeleton, in the muscles responsible for ankle dorsi-plantarflexion such as the gastrocnemius and tibialis anterior. However, there is also an increase in muscular activity when using the AGoRA exoskeleton. In addition, it was possible to observe the considerable improvement made on the new interface, adding comfort and a better weight distribution of the system according to the users in the QUEST and VAS. The parameters agree with those found in the literature, which suggests that the integration of the devices can be used as a baseline for future studies with pathological patients.